A new cardinalfish of the genus Apogonichthyoides (Perciformes, Apogonidae) from Raja Ampat Islands, with a key to species - Fraser, Thomas H.; Allen, Gerald R. (Zootaxa, 2011)
Another deep-water cardinal fish of the genus Apogonichthyoides is described from Fiabacet Island, Western Papua, Indonesia. Collected at 73 m, Apogonichthyoides erdmanni has very distinctive markings on the head and body. It is brown with a dark spot on the body below the anterior lateral line, two slightly darker body bars and darker markings on the head, all similar features to those of the Philippine species Apogonichthyoides uninotatus. The new species has vivid, horizontal dark cheek and post-ocular marks, a small oval spot between the eye and tip of upper preopercular arm, yellowish anal, second dorsal and caudal fins, a narrow basicaudal bar less than 1/3 the length of the caudal peduncle, a vertical bar under the posterior half of the second dorsal-fin base reaching the base of the anal fin, small dark spots on the lower half of the body onto the lower portion of the caudal peduncle and a body spot smaller than the pupil of the eye. Apogonichthyoides uninotatus has a faint diagonal cheek mark, a faint horizontal post-ocular mark, a faint dash between the eye and the tip of the upper preopercular arm, brownish anal, second dorsal and caudal fins, a broad basicaudal bar more than 2/3 the length of the caudal peduncle, a broad body bar as a chevron including all of the second dorsal-fin base reaching the base of the anal fin, no small dark spots on the lower half of body and a body spot larger than the pupil of the eye. A key to twenty-two species of Apogonichthyoides is provided.